Lateral variability of subtidal flow at the mid‐reaches of a macrotidal estuary. Issue 9 (21st September 2017) - Ross, Lauren; Valle‐Levinson, Arnoldo; Sottolichio, Aldo; Huybrechts, Nicolas
Abstract: Transverse variations of tidal and subtidal flow were investigated in a macrotidal and convergent estuary. This was accomplished by combining data analysis of current velocities and water density with numerical modeling at the mid‐reaches of the Gironde Estuary (France). Nonlinear mechanisms responsible for overtide generation and hence subtidal flows were found to vary across the estuary and from neap to spring tides. Subtidal flows were driven by a combination of internal asymmetry, tidal advective accelerations, nonlinear effects of water level variations, quadratic friction, and river discharge. The quarter‐diurnal overtide band (D4) in the flow was generated by internal asymmetry and tidal advective accelerations during neap tide. The ratio of quarter‐diurnal to squared semidiurnal bands (D4/D2 2 ) was largest (>0.3) in sections of the channel showing subtidal outflow. River discharge increased from neap to spring tides causing a subsequent increase of seaward subtidal currents. During spring tide, D4 was generated by tidal advective accelerations and quadratic friction combined with river discharge, rather than by internal asymmetry. The sixth‐diurnal overtide (D6) in the flow was comparable to D4 for both neap and spring tides. Largest D6/D2 3 ratios were found in the shallowest cross‐channel locations during both neap and spring tides. Key Points: Transverse distributions of tidal nonlinearities produce lateral variations of subtidal flow at the mid‐reaches of a macrotidal estuary These tidal asymmetries are generated by different mechanisms from neap to spring tide For both neap and spring tide the sixth‐diurnal (D6) overtide band in the current velocity was comparable to the quarter‐diurnal (D4) band